The Paradoxical Nature of Surrender - Holley, Dorothy E. Adamson (Journal of pastoral care & counseling, 2007)
Surrender is one of the most fundamental, important aspects of spirituality and of integration. It is crucial to our relationship to God, to self, and to others. While surrender is essential for any real attempt at authenticity and integration, it is also one of the most challenging aspects of any spiritual pursuit or endeavor. The inability or unwillingness to surrender is a serious impediment to our relationship with God, with others, and even with ourselves. Paradoxically, there is great freedom and an increased sense of control that is experienced when one is able to surrender. This article explores two themes that the author believes are involved in surrender: fear and trust. Clinical as well as personal examples of the paradoxical nature and transformational power of surrender are offered.